La Contemplatio ad amorem de los ejercicios espirituales en los Directorios del siglo XVI (1540-1599) - Izquierdo LC, Antonio (Alpha Omega, 2010)
In this research, Prof. Izquierdo firstly does an analysis of the contemplation ad amorem, in St. Ignatius’ Spiritual Exercises. Secondly, the same subject is studied in the various Directories of the Spiritual Exercises, written during the XVIth. Century. Finally, the author tries to answer two questions: 1) Is ther anything new in the Directories as regard the contemplation ad amorem? and 2) Why is the contemplation ad amorem only treated by few Directories?